Pembelajaran Sejarah dalam Membangun Historical Awarness dan Sikap Nasionalisme Pada Peserta Didik - Handy, Muhammad Rezky Noor (Lambung Mangkurat University, 2021)
History is the part of human life that tells what happened, who did it, where the incident took place, and how the impact of the incident to date. The current era of globalization is very important regarding the history of education which is very fundamental with the aim to shape the character of the community will have a sense of historical awareness. Literature study in writing this article is the subject of his study. History as a learning medium in which we invite students to think historically like a historian in seeing a historical event to be made a life learning by students in schools, the inculcation of the value of nationalism in history learning can be done by understanding the psychological condition of students in each development that is different from each level. So the teachers need to also implement various forms of strategies and effective learning models also precise at the time of their implementation.